Creation and Expansion of a Multisite Tuberculosis Screening Initiative - Andrew Crawford; Sophia Foroushani; Alexandra Woodbridge; Katherine Carsky; Megan Daniele; Robert Drury; Rebekah Bryne; Juzar Ali (Journal of Student-Run Clinics, 2020)
The Tulane School of Medicine Student-Run Tuberculosis (TB) Program provides TB testing at six sites located in homeless shelters and rehabilitation facilities throughout New Orleans, Louisiana. The program indirectly assists in ensuring housing, as sites require proof of TB testing to maintain residence. The program was created and is operated by medical students. To date, there has not been a comprehensive description of the program’s organization, operation, and expansion. The program has the following goals: (1) provide evidence-based screening and testing for TB in high-risk populations; (2) provide connections to higher care when indicated; (3) allow individuals to maintain residence in the facilities served. Student leaders and physician advisors developed program protocols, an evidence-based TB screening questionnaire, and a referral system with a state-run TB clinic. Since January 2017, 6,198 patients have been evaluated for TB and 693 have been referred to higher care. Additionally, the program provides medical students with the opportunity to gain valuable early clinical exposure. Using this model, future program goals include expansion to provide testing at all similar facilities in New Orleans. In addition, this model may be of use to other medical schools and students who aim to develop and implement similar initiatives.